2020
DOI: 10.1136/tsaco-2020-000487
|View full text |Cite
|
Sign up to set email alerts
|

Acute traumatic injuries of the adrenal gland: results of analysis of the Pennsylvania trauma outcomes study registry

Abstract: BackgroundBlunt injuries to the adrenal glands are considered rare, associated with severe injury, and highly mortal, based on autopsy series and earlier retrospective reviews. Recent studies have reported higher incidence rates associated with lower injury severity and mortality rates.MethodsA 3-year review of the Pennsylvania Trauma Outcomes Study Registry of adults with intra-abdominal injuries after blunt trauma was performed and associated organ injuries, injury parameters and in-hospital mortality were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 24 publications
3
7
2
Order By: Relevance
“…As a result, the right adrenal vein is more susceptible to contusions and oedema, and therefore the right adrenal gland is more likely to undergo acute injury. This appears to be consistent with many reports in the international literature [ 7 ] and is similar in incidence to a large retrospective analysis performed recently by an Australian trauma institute [ 8 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…As a result, the right adrenal vein is more susceptible to contusions and oedema, and therefore the right adrenal gland is more likely to undergo acute injury. This appears to be consistent with many reports in the international literature [ 7 ] and is similar in incidence to a large retrospective analysis performed recently by an Australian trauma institute [ 8 ].…”
Section: Discussionsupporting
confidence: 93%
“…Isolated trauma to the adrenal gland is a rare and underreported injury, with an incidence of between 1.5% and 4% of all adrenal trauma cases [1][2][3][4]. Due to its unique anatomy and the mechanism required to result in an isolated injury, adrenal injury is typically unilateral and right-sided [2,[5][6][7][8]. Adrenal gland injury is rare due to its small size, deep retroperitoneal position, and presence of fatty tissue surrounding it; however, the adrenal glands are vulnerable to bleeding due to their extensive network of collateral circulation [9].…”
Section: Introductionmentioning
confidence: 99%
“…There were few reports comparing the mechanism of injury with and without adrenal injury. The retrospective study by DiGiacomo et al 9 reported that there were no differences. The results of the present study could be explained as the deceleration injury from falls or motorcycle collisions that result in shearing of the juxtamedullary venous sinuses of adrenal glands, rather than direct injury toward the abdomen from wheel injury on motor vehicle crash.…”
Section: Discussionmentioning
confidence: 92%
“…From reports from earlier studies, adrenal trauma is rare. These studies have shown an incidence of up to 2% of adrenal haemorrhage in abdominal traumas 4–6 . Adrenal trauma seems to be associated with more severe injuries and an increased mortality rate 4 .…”
Section: Introductionmentioning
confidence: 99%
“…These studies have shown an incidence of up to 2% of adrenal haemorrhage in abdominal traumas. 4 , 5 , 6 Adrenal trauma seems to be associated with more severe injuries and an increased mortality rate. 4 In postmortem studies, however, the reported incidence of adrenal haemorrhage or injury in trauma patients is higher; 7%–26%.…”
Section: Introductionmentioning
confidence: 99%